Analisis Torsi Sepeda Motor R15V3 2017 Menggunakan 3 Variasi Final Drive Gear - Achmad Rosikh Aminan Abu Amid; Bambang Irawan (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Motorcycles are two-wheeled vehicles that have a fairly high economic value compared to other vehicles in the general public. Motorcycles are formed from several constituent components such as the vehicle frame, engine, transmission, final gear, and wheels. One of them that will be discussed is the use of final gear. The purpose of this study is to determine the amount of torque produced from 3 variations of final gear 13Tx49T, 14Tx48T, 15Tx50T on the 2017 r15v3 motorcycle. From the data obtained, the maximum torque size at the final gear use size 13Tx49T = .... Nm at a speed of 8000 rpm. 14Tx48T = .... Nm at a speed of 8000 rpm. 15Tx50T = .... Nm at a speed of 8000 rpm. Meanwhile, the difference in torque ratio produced by the final gear (standard) size 14Tx48T with the size 15Tx50T the difference in value = ... Nm. final gear size 15Tx50T more (big/small), Large difference in torque ratio size 13Tx49T with size 14Tx48T value difference = ... Nm over (large/small) 14Tx48T, Large difference in torque ratio of size 15Tx50T with size 13Tx49T is value difference = .... Nm larger/smaller 13Tx49T/15Tx50T than 13Tx49T/15Tx50T size.